Novel Wild-Type Pediococcus and Lactiplantibacillus Strains as Probiotic Candidates to Manage Obesity-Associated Insulin Resistance - Paraskevi Somalou; Eleftheria Ieronymaki; Kyriaki Feidaki; Ioanna Prapa; Electra Stylianopoulou; Katerina Spyridopoulou; George Skavdis; Maria E. Grigoriou; Panayiotis Panas; Anagnostis Argiriou; Christos Tsatsanis; Yiannis Kourkoutas (Microorganisms, 2024)
As the food and pharmaceutical industry is continuously seeking new probiotic strains with unique health properties, the aim of the present study was to determine the impact of short-term dietary intervention with novel wild-type strains, isolated from various sources, on high-fat diet (HFD)-induced insulin resistance. Initially, the strains were evaluated in vitro for their ability to survive in simulated gastrointestinal (GI) conditions, for adhesion to Caco-2 cells, for bile salt hydrolase secretion, for cholesterol-lowering and cellular cholesterol-binding ability, and for growth inhibition of food-borne pathogens. In addition, safety criteria were assessed, including hemolytic activity and susceptibility to antibiotics. The in vivo test on insulin resistance showed that mice receiving the HFD supplemented with Pediococcus acidilactici SK (isolated from human feces) or P. acidilactici OLS3-1 strain (isolated from olive fruit) exhibited significantly improved insulin resistance compared to HFD-fed mice or to the normal diet (ND)-fed group.